Molecular regulation of Ezh2 expression - Neo, Wen Hao (Nanyang Technological University, 2013)
A Polycomb Group protein, Ezh2, exerts its epigenetic function through mediating histone H3 Lysine 27 trimethylation and plays an important role in cell fate determination, X-chromosome inactivation, lymphocyte development and cancer progression. Due to the indispensable role of Ezh2 in various biological processes, its expression must be tightly regulated. However, most studies have mainly focused on the transcriptional control of Ezh2 on its target genes. The regulation of Ezh2 expression remains elusive. Therefore, this project is initiated to elucidate the regulatory mechanisms controlling Ezh2 expression in lymphocyte development, activation and neuronal differentiation. In this report, we showed that Ezh2 expression is regulated at both transcriptional and post-transcriptional levels during lymphocyte development and activation. To identify the transcriptional regulators of Ezh2 expression, an Ezh2-EGFP fusion reporter mouse is generated. In parallel, we have identified NF-κB as a regulator of Ezh2 expression by using candidate gene approach and minimal promoter luciferase reporter assay. We showed that overexpression of NF-κB upregulates Ezh2 expression and NF-κB binds to the Ezh2 locus in B and T cells. A fluorescence-based miRNA screening strategy is established to identify potential miRNAs that regulate Ezh2 expression. We have discovered five novel miRNAs including miR-124 that regulate Ezh2 expression. We found that Ezh2 is a functional miR-124 target with relevance to P19 neuronal differentiation. Importantly, miR-124 regulated Ezh2 expression is crucial for optimal P19 neuronal differentiation. Overexpression of Ezh2 which is independent of miR-124 regulation inhibits P19 neuronal differentiation and promotes astrocyte differentiation. In addition, our preliminary data suggest that there is a possible feedback regulatory mechanism between Ezh2 and miR-124. In summary, our results indicate that Ezh2 expression is regulated at both transcriptional and post-transcriptional levels. We demonstrate that Ezh2 expression in lymphocytes is regulated by c-rel. In addition, miR-124 regulated Ezh2 expression is important for neurogenesis.